EVOLUCIÓN TEÓRICA DE GESTIÓN DEL CONOCIMIENTO (2016)
During the last few years knowledge management has been strengthen in those organizations interested in creating competitive advantage in the identification and correct application of the knowledge they generate. The study of knowledge management has been extended into the social, cultural, economic, administrative, and scientific areas resulting in numerous models that have been used in both public and private companies, which have provided useful empirical evidence to further advance its study. In this paper we review some of the many models that have emerged as more scholars research the topic and present some classifications proposed by these researchers. The body of theory about knowledge management is growing, thus we leave this study open to continue to inquire into this matter.